2022
DOI: 10.36660/ijcs.20200279
|View full text |Cite
|
Sign up to set email alerts
|

Use of Diuretics is Associated with Higher Risk of Sarcopenia in Older Adults with Hypertension

Abstract: Sarcopenia is defined as a progressive and generalized loss of skeletal muscle mass and function (i.e., muscle power, muscle strength, and physical performance). [1][2][3][4][5] Since 2016, it has been recognized as a disease. 6 People aged 50 years and older lose 1% of skeletal muscle mass, 2% of gait speed, and 1.9 to 5.0% of handgrip strength per year, 7,8 and these variables have been used for the assessment of sarcopenia by renowned organizations. 9 However, the cause and pathogenesis of sarcopenia are no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…Due to diuretics being one of the classes of medication used to treat hypertension, they have the potential to cause loss of muscle function, thus leading to sarcopenia as they suppress the sodiumpotassium pump. 90 On the other hand, according to a study done by Su et al, 57 diabetes has also been reported as one of the factors associated with sarcopenia, in line with the study done by Qiao et al 91 The loss of motivation and lack of exercise causes muscle loss, resulting in less insulin-responsive target tissue. This will cause a reduction in glucose uptake and utilisation, increasing fat mass, and finally leading to obesity, which repeats the vicious cycle of sarcopenic obesity mentioned above.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Due to diuretics being one of the classes of medication used to treat hypertension, they have the potential to cause loss of muscle function, thus leading to sarcopenia as they suppress the sodiumpotassium pump. 90 On the other hand, according to a study done by Su et al, 57 diabetes has also been reported as one of the factors associated with sarcopenia, in line with the study done by Qiao et al 91 The loss of motivation and lack of exercise causes muscle loss, resulting in less insulin-responsive target tissue. This will cause a reduction in glucose uptake and utilisation, increasing fat mass, and finally leading to obesity, which repeats the vicious cycle of sarcopenic obesity mentioned above.…”
Section: Discussionmentioning
confidence: 54%
“…One study also found that the prescription of diuretics and their usage among older adults also cause a higher risk of sarcopenia in older adults with hypertension. Due to diuretics being one of the classes of medication used to treat hypertension, they have the potential to cause loss of muscle function, thus leading to sarcopenia as they suppress the sodium‐potassium pump 90 . On the other hand, according to a study done by Su et al, 57 diabetes has also been reported as one of the factors associated with sarcopenia, in line with the study done by Qiao et al 91 The loss of motivation and lack of exercise causes muscle loss, resulting in less insulin‐responsive target tissue.…”
Section: Discussionmentioning
confidence: 99%
“…5 Recently, an original article was published that evaluated 129 elderly patients with hypertension, concluding that handgrip strength was a good method for evaluating sarcopenia and that the use of diuretics in the treatment of hypertension in these patients was associated with an increase sarcopenia. 6 This was an unprecedented finding in the literature for this population, and it warrants analysis and reflection.…”
mentioning
confidence: 84%